Extracellular Matrix Modulates Outgrowth Dynamics in Ovarian Cancer. Issue 12 (9th September 2022) - Alshehri, Sarah; Pavlovič, Tonja; Farsinejad, Sadaf; Behboodi, Panteha; Quan, Li; Centeno, Daniel; Kung, Douglas; Rezler, Marta; Lee, Woo; Jasiński, Piotr; Dziabaszewska, Elżbieta; Nowak‐Markwitz, Ewa; et al.
Abstract: Ovarian carcinoma (OC) forms outgrowths that extend from the outer surface of an afflicted organ into the peritoneum. OC outgrowth formation is poorly understood due to the limited availability of cell culture models examining the behavior of cells that form outgrowths. Prompted by immunochemical evaluation of extracellular matrix (ECM) components in human tissues, laminin and collagen‐rich ECM‐reconstituted cell culture models amenable to studies of cell clusters that can form outgrowths are developed. It is demonstrated that ECM promotes outgrowth formation in fallopian tube non‐ciliated epithelial cells (FNE) expressing mutant p53 and various OC cell lines. Outgrowths are initiated by cells that underwent outward translocation and retained the ability to intercalate into mesothelial cell monolayers. Electron microscopy, optical coherence tomography, and small amplitude oscillatory shear experiments reveal that increased ECM levels led to increased fibrous network thickness and high shear elasticity of the microenvironment. These physical characteristics are associated with outgrowth suppression. The low ECM microenvironment mimicks the viscoelasticity of malignant peritoneal fluid (ascites) and supports cell proliferation, cell translocation, and outgrowth formation. These results highlight the importance of the ECM microenvironment in modulating OC growth and can provide additional insights into the mode of dissemination of primary and recurrent ovarian tumors. Abstract : This study investigates the importance of varying extracellular matrix concentrations in modulating ovarian cancer growth. It demonstrates that the extracellular matrix promotes outgrowth formation in fallopian tube non‐ciliated epithelial cells expressing mutant p53 and various ovarian cancer cell lines. Low concentrations of extracellular matrix mimic viscoelasticity of malignant peritoneal fluids and support cell proliferation, cell translocation, and outgrowth formation.